An Approach to the Legal Analysis of the Transparency of Judicial-Administrative Precedents in the Judiciary; Emphasizing the Prevention of Corruption - Ahmad Alinezhad; Ahmad Rafiei; Hojjatollah Alamolhoda,, (دانش حقوق عمومی)
One of the continuous concerns of human society, which is especially considered by legal and social science experts today and is interpreted as a basic component in good governance, is combating the phenomenon of ‘corruption’. The dangerous place of the judicial system and the need for the health of the judiciary from corruption, which will cause the eradication of corruption, oppression and discrimination, immorality and other corrupting factors in the society, lead us to the fact that we should look for a solution to prevent corruption in the judiciary. Transparency is one of the important and influential components in dealing with corruption. The main question of the research is based on the proposition that "from the point of view of transparency, in a general sense, what results can be obtained regarding the existing processes in the judiciary (judicial-administrative) that will result in the reduction or deterrence of corruption?" The present research, using a descriptive-analytical method, regarding the data collected by the library method with the definition and division of the concept of transparency in the field of affairs related to the judiciary into two categories, administrative and judicial, with the necessity of adopting solutions such as strengthening the information systems of officials' property Judiciary, clarifying the process of appointment of judges, free publication of judicial opinions by the judiciary and the like, which their application will lead to the improvement of indicators of deterrence from corruption in the judiciary.